Identification of Firm Multiplier of Comparable Firm Valuation Method on Indonesian IPO - Andrew Handaya; Dezie L. Warganegara; Doni S. Warganegara (Bina Nusantara University, 2009)
The aim of this research is to find the relevant valuation measurement, firm multiplier, which is utilized by issuers or underwriters during IPO. This research uses companies that conducted IPO, in the Indonesia Stock Exchange (IDX), within year 2001 to 2007, as the research sample. The hypotheses are developed to find the relevant valuation multiplier. The data are analyzed using One-Sample T Test, Kolmogorov-Smirnov (K-S) Test, and Binomial Test. The empirical results suggest that there are similarities and differences in valuation results when comparable firm valuation is utilizing different firm multiplier. Among the five methods, i.e. arithmetic mean, median, harmonic mean, closest ROA, and closest TA, the closest TA method performs the worst in Indonesia capital market during 2001-2007. There is no statistical difference between selecting arithmetic mean, median, and harmonic mean methods. The closest ROA method outperforms the arithmetic mean and closest TA methods; however it has similar performance to median and harmonic mean methods.